Ethnobiology of Corals and Coral Reefs - Narchi, Nemer; Price, Lisa Leimar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book explores the ethnobiology of corals by examining the various ways in which humans, past and present, have exploited and taken care of coral and coralline habitats.  This book will bring the educated general audience closer to corals by exploring the various circumstances of human-coral coexistence by providing scientifically sound and jargon-free perspectives and experiences from across the globe. Corals are a vital part of the marine environment since they promote and sustain marine and global biodiversity while providing numerous other environmental and cultural services. Countless valuable coral conservation efforts are published in academic and general audience venues on a daily basis. However relevant, few of these reports show a direct, deeper understanding of the intimate relationship between people and corals throughout the world’s societies. Ethnobiology of Corals and Coral Reefs establishes an intimate bond between the audience and the wonder of corals and their importance to humankind.
Introduction -- Seeing corals with Darwin’s eyes of reason -- The reef sulphur cycle: influence on climate and ecosystem services -- Symbols at War: The impact of Corallium rubrum in the Indo-Pakistani subcontinent -- Ethnobiology of Corallium rubrum: Protection, healing, medicine, and magic -- Corals and coralline organisms in Seri culture: Traditional and modern uses -- Puka Mai He Ko’a: The significance of corals in Hawaiian culture -- Coral gardens of the Dumo people of Papua New Guinea: a preliminary account -- The catch of Maui: Coral gardens in the past and present of the Tongan islands -- Change in Roviana Lagoon coral reef ethnobiology -- Rocky reefs: Preserving biodiversity for the benefit of the communities in the Aquarium of the World -- Conservation of corals in the Colombian Caribbean.
Keywords: Aquatic ecology .; Marine sciences; Freshwater; Animal systematics; Animal taxonomy; Freshwater & Marine Ecology; Marine & Freshwater Sciences; Animal Systematics/Taxonomy/Biogeography.